Uganda : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper describes Uganda's experience under the 2013 Policy Support Instrument (PSI). The current 2013 PSI was approved by the IMF's Executive Board in June 2013 with an initial duration of three years. Overall, performance under this PSI has been assessed to be satisfactory. Most quantitative assessment criteria were met, and macroeconomic stability maintained. However, the pace of structural reforms slowed down compared with the past, and only about half of the structural benchmarks were ultimately met. The experience shows the importance of ensuring commitment to the reforms, explaining them better, and getting broad-based buy-in to achieve progress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet